Female Genital Mutilation and Primary Healthcare Services: A Narrative Review - Ozden Gokdemır; Barlas Efe Yılmaz; Bruna Martins; Lara Domingues Diogo; Helena Alonso-Valencia; Mariana José Silva; Ana Peral Martín (Turkish Journal of Family Medicine and Primary Care, 2026)
Background:Female genital mutilation (FGM) includes all non-medical procedures that involve partial or complete removal of the external female genitalia, or any injury to the female genital organs. The World Health Organization (WHO) classifies FGM into four types and recognizes it as an internationally condemned violation of the human rights of girls and women.Objective:To synthesize recent evidence on the classification, global epidemiology, health consequences and primary-care implications of FGM, with particular attention to family physicians, midwives and primary-care nurses caring for immigrant women and girls living in Türkiye.Methods:Narrative review of articles published in English or Turkish between January 2000 and January 2026, identified through PubMed/MEDLINE, Web of Science, Scopus, Google Scholar, the Cochrane Library and DergiPark. Reports and guidelines from WHO, UNICEF and the United Nations Population Fund (UNFPA) were hand-searched for additional grey literature. Emphasis was placed on systematic reviews, meta-analyses, guidelines and policy documents published between 2020 and 2025.Results:Over 230 million girls and women alive today have undergone FGM. The practice is concentrated in approximately 30 countries and is increasingly relevant in host countries because of migration. Recent evidence confirms associations between FGM and obstetric, urological, sexual, psychological and other long-term health complications. Evidence for an association with infertility is suggestive but not definitive. Health-education interventions delivered through trusted community and primary-care channels may reduce the intention to perform FGM in future generations.Conclusion:Although FGM is not part of Türkiye's traditional culture and nationally representative prevalence data are unavailable, primary-care physicians in Türkiye may encounter affected women and girls because of migration from high-prevalence countries. Family physicians, midwives and primary-care nurses are therefore essential to case identification, trauma-informed and culturally sensitive counseling, appropriate referral, and community-level prevention. Targeted health-education programs for immigrant communities from high-prevalence countries are recommended as a primary, non-medical strategy to reduce the practice and its complications.